Sulfur compounds navigate redox processes, leukotriene synthesis, and ω-hydroxylation of leukotriene B4 in neutrophil interaction with the bacteria Salmonella typhimurium: the way to manipulate neutrophil swarming - Golenkina, Ekaterina A.; Navarnova, Sofia V.; Viryasova, Galina M.; Galkina, Svetlana I.; Gaponova, Tatjana V.; Romanova, Yulia M.; Sud’ina, Galina F. (Frontiers in Immunology, 2025)
Neutrophils are the first immune cells recruited by invading pathogens. During interaction with bacteria, neutrophils synthesize leukotriene B4, a potent chemoattractant that, in conjunction with the primary bacterial chemoattractant N-formyl-l-methionyl-l-leucyl-l-phenylalanine (fMLP), stimulates the formation of neutrophil clusters surrounding pathogens. Hydrogen sulfide (H2S) plays a critical role in the regulation of host–bacteria interactions, and bacteria are known to use H2S in response to host-induced oxidative stress. The purpose of this study was to investigate the regulatory role of H2S in neutrophil cellular responses in an experimental model of neutrophil interaction with Salmonella typhimurium. The application of H2S donor (sodium hydrosulfide hydrate, NaSH) during the interaction of neutrophils with bacteria increased the leukotriene synthesis stimulated by the peptide fMLP. NaSH significantly suppressed the reactive oxygen species (ROS) formation in neutrophils. When phorbol-12-myristate-13-acetate (PMA) was used in cell pretreatment before the addition of fMLP, a decreased leukotriene synthesis and an increased ROS formation in cells were observed. Not producing ROS disulfide stress induced by diamide, in combination with NaSH, synergistically increased the fMLP-induced leukotriene synthesis during the interaction of neutrophils with the bacteria S. typhimurium. The data obtained demonstrate that not producing ROS disulfide stress increases leukotriene synthesis in the presence of H2S-producing compounds.